The effects of electric impulse on growth of Rhizophora mucronata seedlings (Rhizophorales: Rhizophoraceae) - Kathiresan, K (Universidad de Costa Rica, 2000)
Exposure of mangrove seedlings to electric current was studied at an intensity of 10, 20 and 30 mA to 0.5, 1, 3, 6, 12 and 24 h in different combinations, either to plumule or radicle or both parts of the propagules of Rhizophora mucronata Poir (sample size = 30). The electric current-treated propagules and untreated control were cultured hydroponically in sea water for 75 days, and root and shoot growth parameters measured. The root elongation was significantly influenced by duration of exposure, site of propagule treated and combined effects of current intensity x site of propagule treated. Leaf number and area were significantly influenced by intensity of electric current and duration of exposure; whereas shoot elongation was affected by the duration of exposure. The root number was significantly affected by duration of exposure. In general, the electric impulse improved the growth characteristics of shoot and root.